2023
DOI: 10.1186/s13058-023-01602-x
|View full text |Cite|
|
Sign up to set email alerts
|

A prospective case–cohort analysis of plasma metabolites and breast cancer risk

Abstract: Background Breast cancer incidence rates have not declined despite an improvement in risk prediction and the identification of modifiable risk factors, suggesting the need to identify novel risk factors and etiological pathways involved in this cancer. Metabolomics has emerged as a promising tool to find circulating metabolites associated with breast cancer risk. Methods Untargeted metabolomic analysis was done on prediagnostic plasma samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, in eight prospective studies 82,[154][155][156][157][158][159][160] , 13 individual metabolites were identified that replicably associate with risk of postmenopausal breast cancer, most of which also correlate with BMI 82,161,162 . These include several understudied sex steroid hormone metabolites whose association with breast cancer risk was nevertheless independent from oestradiol and dehydroepiandrosterone (DHEA)sulphate 82,155 , one of which (16α-hydroxy DHEA 3-sulphate) mediated 34% of the BMI-breast cancer relationship 82 .…”
Section: "Omics"-identified Biologic Factorsmentioning
confidence: 99%
“…For example, in eight prospective studies 82,[154][155][156][157][158][159][160] , 13 individual metabolites were identified that replicably associate with risk of postmenopausal breast cancer, most of which also correlate with BMI 82,161,162 . These include several understudied sex steroid hormone metabolites whose association with breast cancer risk was nevertheless independent from oestradiol and dehydroepiandrosterone (DHEA)sulphate 82,155 , one of which (16α-hydroxy DHEA 3-sulphate) mediated 34% of the BMI-breast cancer relationship 82 .…”
Section: "Omics"-identified Biologic Factorsmentioning
confidence: 99%
“…Stevens et al [ 93 ] found that Gln was associated with a reduced risk of breast cancer, as in studies involving pre- and postmenopausal women in EPIC [ 93 ], but other studies produced conflicting results. Gln was associated with an increased risk in the SU.VI.MAX [ 95 ] and E3N [ 92 ] cohorts, where the association was limited to premenopausal women.…”
Section: Diagnostic Value Of Determination Of Amino Acids In Biologic...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors would like to correct the Acknowledgements section.…”
mentioning
confidence: 99%